Combined artificial tear medications in the treatment of patients with dry eye syndrome - V. V. Brzhesky (Российский офтальмологический журнал)
In the treatment of patients with dry eye syndrome, the main measure is tear replacement therapy, the most accessible for practicing physicians. It is understandably based on the instillations of artificial tear medications, whose number is steadily growing. In Russia, there are 47 registered medications of this type. Considering the set of requirements for artificial tear medications (which are expected to moisturize the ocular surface, stop the hyperosmolarity of the tear film, ensure osmo-protection and reduce inflammation in the tissues of the ocular surface, as well as activate their reparative regeneration), the most promising medications are those containing two or more active ingredients. One such medication is Oftolik ® medium-viscosity tear substitute that contains a combination of 1.4 % polyvinyl alcohol and 0.6 % polyvinylpyrrolidone. The moisturizing effect of these polymers is complemented by reparative regeneration stimulation (polyvinyl alcohol) and the production of endogenous interferon (polyvinylpyrrolidone). Multiple studies confirmed high clinical efficacy of the medication for the treatment of patients with the main pathogenetic types of dry eye syndrome, as well as its syndromal and secondary symptomatic forms (computer visual syndrome) and revealed. As these effects are achieved with no significant side effects, we can recommend Oftolik® and its preservative-free form Oftolik BK ® for wide clinical use.